Gambaran Kesejahteraan Subjektif Siswa Pengguna Media Sosial SMA Negeri se-Kecamatan Karanganyar - Fristya Qusnul Saputri; Mulawarman (Universitas Pendidikan Ganesha, 2022)
Subjective well-being in using social media affects mental health in students. The research objective is to describe the subjective well-being of students using social media. The method used is descriptive quantitative with a sample of 303 students using social media. The instrument used is the subjective well-being scale with a validity coefficient of 0.356 to 0.739 and a reliability of 0.759. The results obtained through descriptive statistical analysis, the subjective well-being level of students using social media are in the moderate category (M = 41.01, SD = 3.66). Based on these results, it is expected to be a reference for BK teachers in providing interventions, services and support to students who use social media to improve their subjective well-being.